Uma abordagem nebulosa para avaliar o impacto de geradores independentes eólicos no despacho integrado do sistema. - Mangueira, Heitor Hugo Dias (2005)
In this work, the spread of the uncertainties of wind power generation systems on a network is evaluated. The study uses a flow of power foggy multi-linearized.